The intelligibility of nature : how science makes sense of the world - Dear, Peter, 1958- (Science.culture., 2006)
Throughout the history of the Western world, science has possessed an extraordinary amount of authority and prestige. And while its pedestal has been jostled by numerous evolutions and revolutions, science has always managed to maintain its stronghold as the knowing enterprise that explains how the natural world works: we treat such legendary scientists as Galileo, Newton, Darwin, and Einstein with admiration and reverence because they offer profound and sustaining insight into the meaning of the universe. In The Intelligibility of Nature, Peter Dear considers how science as such has evolved a.